Self-leadership balancing-based career guidance and counseling model in career planning - Nini; Ristam; Hastiani (Universitas Sarjanawiyata Tamansiswa, 2024)
The instant gratification situation makes students experience career problems, where they want a career that is work-life balanced with their current character and life. The purpose of this research is to see the profile of balancing self-leadership in career planning of students of SMP Negeri Teluk Keramat District and Career Counseling Model based on balancing self-leadership in career planning of students of SMP Negeri Teluk Keramat District. The method used in this research is the ADDIE R&D model. Based on the above opinion, it can be concluded that students have expectations of the career choices that will be taken, so balancing self-leadership is needed in career planning so that the desired work-life balance can be achieved The results of this study are the achievement of the skill aspects to be achieved in the implementation of this model where students understand themselves so that they can explore the potential that exists within themselves, as well as knowing the obstacles and challenges in the process of achieving a career, and can design a future career after seeing and discussing job opportunities with their friends, so it can be concluded that this model can be used properly as one of the supporting books in career services based on balancing self- leadership in career planning. The implication of this research is to develop students' self-leadership in the field of careers at school as one of the steps in career planning which will have an effective influence on career decision making